Crisis Management of Regional Development: Cluster Initiatives in Russia and their Efficiency - VASENEV, Sergey L.; OVANESYAN, Natalya M.; ROSSINSKAYA, Marina V.; VOLGINA, Svetlana V.; ROKOTYANSKAYA, Violetta V. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The article reports results of research investigating cluster initiatives as a tool for crisis management at the regional level. The indicator helping to assess the regional industrial policy impact has been identified. Based on its values, the federal districts of Russia were classified according to the types of effectiveness of regional crisis management. The key problems of Central and North-Western federal districts were identified. The expediency of studying cluster initiatives of the Central Federal District since its historical development and scale of its regional economies are comparable to European parameters. The study of cluster initiatives allowed to find the cluster initiatives management scheme typical for the practice of stimulating clustering processes embedded in the strategies of social and economic development of the subjects of the Russian Federation. A quantitative assessment of existing and potential clusters has been carried out on the example of the subjects of the Central Federal District, cluster initiatives have been ranked by types of economic activity. Cluster initiatives were differentiated according to the specifics of the management processes, and the specific nature of cluster initiatives. A factual basis for indicators has been formed in line with the objectives of the cluster policy of the Central Federal District subject. Having compared the indicators of the cluster initiatives specification with the values of the cluster policy implementation indicators, we analyzed the efficiency of cluster initiatives as an element of the regional crisis management.